2002
DOI: 10.2113/gscanmin.40.6.1649
|View full text |Cite
|
Sign up to set email alerts
|

MONAZITE-(Sm), A NEW MEMBER OF THE MONAZITE GROUP FROM THE ANNIE CLAIM #3 GRANITIC PEGMATITE, SOUTHEASTERN MANITOBA

Abstract: Monazite-(Sm) was found in the Annie Claim #3 pod of lepidolite-subtype granitic pegmatite within the Greer Lake intrusion of pegmatitic leucogranite, in the Archean Bird River Subprovince of the Superior Province, in southeastern Manitoba. It occurs as tabular crystals ≤0.4 mm in diameter, associated with manganocolumbite, quartz, albite and lithian muscovite. Monazite-(Sm) is yellowish, translucent, with a white streak, vitreous to greasy luster, and no observed fluorescence. One good cleavage is present, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Monazite solid-solution, in which Sm is the predominant REE, is very rare and monazite-(Sm) has been described as a new species only recently (Masau et al, 2002). In the vast majority of cases, the lighter REE (Ce in particular) are predominant and a Nd/Sm ratio of approximately 10 appears to be common (Zhu and O'Nions, 1999).…”
Section: Application To Natural Systemsmentioning
confidence: 99%
“…Monazite solid-solution, in which Sm is the predominant REE, is very rare and monazite-(Sm) has been described as a new species only recently (Masau et al, 2002). In the vast majority of cases, the lighter REE (Ce in particular) are predominant and a Nd/Sm ratio of approximately 10 appears to be common (Zhu and O'Nions, 1999).…”
Section: Application To Natural Systemsmentioning
confidence: 99%
“…Coloured lines indicate the field boundaries for dominant Sm (red and blue) and Yb (all others). Data sources: Masau et al (2002), Repina et al (2011), Voloshin et al (1984), Voloshin et al (1983), Simmons et al (2006) and Buck et al (1999). …”
Section: Resultsmentioning
confidence: 99%
“…Table 3: a, long columnar zircon crystal from kaolinized biotite granite (the older intrusive complex of the Nejdek pluton, NEP1), borehole GS7/248 near Sokolov; b, patchy zoned zircon enclosed in chlorite from biotite granite (the older intrusive complex of the Nejdek pluton, NEP1), borehole KP 59/06 near Královské Poříčí; c, oscillatory zoned zircon from the coarsegrained Li-biotite-topaz granite (the younger intrusive complex of the Nejdek pluton, NEP2), near Horní Blatná; d, zoned zircon crystal enclosed in biotite from porphyritic fine-grained biotite granite (the younger intrusive complex of the Nejdek pluton, NEP2), Karlovy VaryTuhnice; e, several small zircon crystals associated with apatite, ilmenite and monazite embedded in biotite and muscovite, fine-grained biotitemuscovite Lipnice-type granite (MP1), Lipnice; f, small zircon crystals associated with large apatite, ilmenite and monazite enclosed in biotite, medium-grained biotite-muscovite Kouty-type granite (MP2), Kouty; g, zoned zircon crystal enclosed in altered plagioclase from coarse-grained two-mica Melechov-type granite (MP2), Melechov hill; h, association of monazite, zircon, apatite and ilmenite in the porphyritic biotite Steinbergtype granite (PPP1), Pendelin, Austria; i, association of zircon and monazite crystals with apatite, coarse-grained two-mica Plechý-type granite (PPP2), Trojmezná hill; j, monazite (white) and several zoned zircon crystal (gray) enclosed in biotite, porphyritic fine-grained biotite granite (the younger intrusive complex of the Nejdek pluton, NEP2), Karlovy Vary-Tuhnice; k, cheralite (white) and two fragments of zoned zircon enclosed in kaolinite, kaolinized biotite granite (the older intrusive complex of the Nejdek pluton, NEP1), borehole GS7/248 near Sokolov; l, altered and partly altered monazite grain (white) associated with fragments of zoned zircon (gray) and rounded aggregate of organogenic pyrite, kaolinitized biotite granite (the older intrusive complex of the Nejdek pluton, NEP1), borehole GS7/248 near Sokolov lowest (approximately 0.7) were in the PPP1 granites. Monazite varieties with prevailing La (monazite-(La)) or another REE are rare (Graeser and Schwander 1987;Masau et al 2002) and were not identified in the studied set of rocks. It is worth noting that the overall correlation between La and Ce is positive (Fig.…”
Section: Monazite-(ce)mentioning
confidence: 99%